Lithium Treatment Over the Lifespan in Bipolar Disorders - Volkmann, Constantin; Bschor, Tom; Köhler, Stephan (Frontiers in Psychiatry, 2020)
Lithium has been the treatment of choice for patients with bipolar disorder (BD) for nearly 70 years. It is recommended by all relevant guidelines as a first-line treatment for maintenance therapy. In this review, we outline the current state of evidence for lithium in the treatment of BD over the lifespan. First, we summarize the evidence on efficacy in general, from relapse prevention to acute anti-manic treatment and its role in treating mood episodes with mixed features and bipolar depression. As patients are often treated for many years and different aspects have to be considered in different phases of life, we discuss the particularities of lithium in the treatment of paediatric bipolar disorder, in older aged individuals and in pregnant women. Lastly, we discuss the evidence on lithium’s proposed suicide-preventive effects, the dangers of rapid discontinuation and lithium’s adverse effects, particularly with regard to long-term treatment.